Carbon flow tracking and network reconfiguration: a network evolution analysis of embodied carbon emissions from belt and road trade under regional and industry perspectives - Wang, Ying; Zhang, Ruohan; Wang, Shali; Wang, Liya; Dai, Xinglan; Zu, Zishuai (Frontiers in Sustainable Cities, 2025)
The Belt and Road (B&R) initiative has strengthened trade ties among participating nations over the past decade, while contributing over 50% of global carbon footprint, which has exerted growing pressure on climate governance. This paper uses the multi-regional input–output (MRIO) model to build the B&R trade embodied carbon emission network across 66 countries and 26 industrial sectors from 2004 to 2020, and combines social network analysis to observe the flow relationship and evolution process from the regional and industry perspective. The research shows that in 2020, the total carbon emissions of countries along the B&R increased by 66% compared with 2004, the trade links were closer, and the connectivity of the embodied carbon network was gradually enhanced. China, India, and Russia are at the core of the network, with countries such as China, Russia and UAE playing a bridging role. Carbon leakage has gradually shifted from China to Southeast Asian countries with relatively lenient environmental regulations such as India and Vietnam. From the perspective of industry, the B&R industrial agglomeration effect is strengthened, and the carbon link can be reached quickly. Industries such as electricity, gas and water dominate the network, while electrical and machinery plays important regulatory function, exerting strong control over embodied carbon flows across sectors. The findings offer a factual basis for B&R countries to coordinate cross-regional and cross-sector carbon emission control, clarifying emission responsibilities, identifying reduction pathways, and promoting the high-quality construction of the B&R.